2014
DOI: 10.1101/cshperspect.a013656
|View full text |Cite
|
Sign up to set email alerts
|

Diversification and Specialization of Touch Receptors in Skin

Abstract: Our skin is the furthest outpost of the nervous system and a primary sensor for harmful and innocuous external stimuli. As a multifunctional sensory organ, the skin manifests a diverse and highly specialized array of mechanosensitive neurons with complex terminals, or end organs, which are able to discriminate different sensory stimuli and encode this information for appropriate central processing. Historically, the basis for this diversity of sensory specializations has been poorly understood. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 109 publications
(123 reference statements)
3
70
0
Order By: Relevance
“…Similar to audition, vision, olfaction, and taste, mechanosensitivity provides a necessary means of receiving information about the environment. However, mechanosensitivity is the least understood modality at both the cellular and the molecular level (31,32). We have demonstrated that, to our knowledge, tactileforaging birds possess the largest-yet-reported number of TG neurons expressing the Piezo2 mechanotransducer.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similar to audition, vision, olfaction, and taste, mechanosensitivity provides a necessary means of receiving information about the environment. However, mechanosensitivity is the least understood modality at both the cellular and the molecular level (31,32). We have demonstrated that, to our knowledge, tactileforaging birds possess the largest-yet-reported number of TG neurons expressing the Piezo2 mechanotransducer.…”
Section: Discussionmentioning
confidence: 90%
“…With the exception of the bill tip organ, where Grandry and Herbst mechanoreceptors are encapsulated in papillae, the majority of mechanoreceptors in the dorsal and ventral surfaces of the duck bill skin are located ∼50-100 μm below the basal layer of the dermis (4). In this sense, the position of the Grandry and Herbst mechanoreceptors is analogous to all other types of mechanoreceptors in the glabrous skin of vertebrates (31,32). Therefore, the primary afferents that innervate the mechanoreceptors can directly participate in the detection of mechanical stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…Merkel cell differentiation is a temporally regulated process during which early specified Merkel cells start to express transcription factors essential for Merkel differentiation (Atoh1, Sox2, and Isl1), cytoskeletal proteins (Krt8, Krt18, and Krt20), and components of the synaptic machinery (Rab3c), and undergo innervation by sensory neurons expressing neurofilament NF200 (Haeberle et al , 2004; Owens and Lumpkin, 2014; Perdigoto et al , 2014a; Vielkind et al , 1995). …”
Section: Resultsmentioning
confidence: 99%
“…Specialization promotes organismal development and survival by permitting cells to differentiate into cellular lineages that possess unique properties, such as sensation, secretion, absorption, or conductivity [1]. Multicellular organisms coordinate these activities to sustain homeostasis.…”
Section: Introductionmentioning
confidence: 99%